Effects of rosuvastatin and allopurinol on circulating endothelial progenitor cells in patients with congestive heart failure: The impact of inflammatory process and oxidative stress - Tousoulis, D.; Andreou, I.; Tsiatas, M.; Miliou, A.; Tentolouris, C.; Siasos, G.; Papageorgiou, N.; Papadimitriou, C.A.; Dimopoulos, M.-A.; Stefanadis, C. (Atherosclerosis, 2011)
Objective: Endothelial progenitor cells (EPCs) contribute to the maintenance of endothelial integrity and function. We investigated the effects of rosuvastatin and allopurinol on the number of EPCs in patients with heart failure and aimed to provide insight into the molecular inflammatory and oxidative mechanisms that could be responsible for the alterations in EPC levels after treatment. Methods: Sixty patients with systolic heart failure were randomized to receive rosuvastatin 10mg/d, allopurinol 300mg/d or placebo and followed up for 1 month. The number of CD34 +/KDR + and CD34 +/CD133 +/KDR + EPCs in blood was evaluated by flow cytometry. Endothelial function was assessed by brachial artery flow-mediated dilation. Levels of markers of inflammation and oxidative stress were also determined. Results: Circulating EPCs were significantly increased after rosuvastatin treatment (from 230 (170-380) and 10 (8-24) to 390 (230-520) and 19 (8-33) cells/10 6 lymphomonocytes, respectively, p=0.004 and p=0.008), whereas they remained unchanged in the other groups. The increase in EPC levels was not associated with the changes in the levels of the measured inflammatory and oxidative markers. Conclusion: Short-term treatment with rosuvastatin, but not allopurinol, significantly increases the number of circulating EPCs in patients with heart failure providing further insights into its role in these individuals. The impact of rosuvastatin on EPCs is not mediated by changes in inflammatory and oxidative status. © 2010 Elsevier Ireland Ltd.
Keywords: Endothelial progenitor cells; Heart failure; Myeloperoxidase; statins; Xanthine oxidase inhibitors